Cogeneration in a solid-wastes power-station: a case-study - de Holanda, M. R.; Balestieri, José Antônio Perrella [UNESP] (Elsevier B.V., 1999)
Nowadays, natural gas is viewed as the solution to the problem of energy supply for Latin America, Europe and North America for the next few decades; Brazil is increasingly becoming dependent upon the Bolivian natural-gas supply - many industries and some entrepreneurs are deciding to construct industrial cogeneration systems and new thermal power-stations burning natural gas because of its low environmental impact and attractive price. However, natural gas is a finite resource: this will cause, in the future, an increase of its unit price. This paper details questions involved in the energy generation and presents solid-waste burning as a possible alternative fuel for the future, especially in the context of cogeneration practice in which the thermal and electric energy are used primarily for the industries located in an industrial district. Two cogeneration schemes are proposed for the burning of municipal solid wastes, associated or not with natural gas, and their technical and economic feasibilities are examined. (C) 1999 Elsevier B.V. Ltd. All rights reserved.